What are ideas made of? On the socio-materiality of creative processes - Rudnicki, Seweryn (Creativity Studies, 2021)
This article explores the possibility that ideas are dynamic, socio-material and relational entities that come into existence with the help of materials and technologies. It starts from arguing that the popular understanding of ideas as immaterial entities (thoughts, concepts, insights) that we process mentally, communicate (symbolically) to others, and eventually realise is rooted in essentialist and representationalist philosophy and as such is not universal. It is then argued that an alternative understanding of what an idea is may be proposed within the relationist perspective that focuses our attention primarily on change and historicity. The article employs the concept of translation – borrowed from the actor-network theory – to propose that an idea is enacted slightly differently in every social situation and with the use of different materials and technologies. Importantly, the presented relational and socio-material interpretation emphasizes that it is not the “essence” of an idea but the translations it is subjected to that enable or constrain action possibilities and determine its evolution. Finally, it is proposed that following translations of ideas empirically may be a promising avenue for further research.